Concurrent Pancreatic Head and Tail Arteriovenous Malformations in a 40-Year-Old Gentleman: The First Published Report - Alnajjar, Asma; Abu-Zaid, Ahmed; Al-omem, Dina A; Aloufi, Daniah S; Azzam, Ayman; Amin, Tarek (JOP. Journal of the Pancreas, 2014)
Context Pancreatic arteriovenous malformations (AVMs) are uncommon in the gastrointestinal tract. Less than 100 cases have been identified in the medical literature. Approximately 10% of all pancreatic AVMs are sporadic. Case Report Herein, we report the first documented case of sporadic concurrent pancreatic head and tail AVMs in a 40-year-old gentleman who presented with a 10-day history of epigastric pain and one episode of hematemesis. Patient denied any history of traumatic incidents, cigarette smoking, alcohol abuse, chronic gastric/duodenal ulcer, chronic pancreatitis, chronic hepatic disease, difficulty swallowing, respiratory compromise, or weight loss. Physical examination and laboratory results were unremarkable. Contrast-enhanced computed tomography scan showed two hypervascular masses involving the pancreatic head and tail. The celiac trunk angiogram showed proliferating vascular networks involving the pancreatic head and tail. The superior mesenteric angiogram demonstrated significant vascular contribution to the pancreatic head arteriovenous malformation only. Due to the extreme locations of pancreatic AVMs in the head and tail, surgical resection of both lesions (leaving behind the normal pancreatic body) was not possible. Instead, patient underwent intraoperative irradiation therapy (IORT). During the procedure, patient was surgically operated to retract healthy organs/tissues, and then a single concentrated dose of radiation therapy was precisely applied to both pancreatic head and tail AVM lesions. Patient had an uneventful postoperative recovery and was discharged home on the second postoperative day in stable condition. The patient is to be seen in clinic in a 4-month-period during which patient will be completing a 12-month period of postoperative IORT. Conclusion This is the first documented case of sporadic concurrent pancreatic head and tail AVMs. Angiography is the gold standard diagnostic modality. Image: Two large vascular arteriovenous malformations involving both the pancreatic head and tail.